Wide QRS Complex Tachycardia in the Emergency Setting - Oreto, Giuseppe; Luzza, Francesco; Satullo, Gaetano; Donato, Antonino; Carbone, Vincenzo; Calabrò, Maria Pia (The Arrhythmic Patient in the Emergency Department, 2016)
A wide QRS complex tachycardia can be (1) ventricular tachycardia (VT); (2) supraventricular tachycardia (SVT) with bundle branch block that may be either preexisting or due to aberrant conduction, namely, tachycardia-dependent abnormal intraventricular conduction; a further possibility is the effect of some antiarrhythmic drugs that slow down intraventricular conduction, resulting in marked QRS complex widening; and (3) supraventricular tachycardia with conduction of impulses to the ventricles over an accessory pathway (preexcited tachycardia).